Prioritisation on labour ward. Issue 10 (October 2019) - Garner, Jessica; Murray, Sebastian; Parisaei, Maryam
Abstract: Labour ward is a demanding and rewarding area of specialised work. It requires a specific skillset, of which one of the most important is knowing how to prioritise. The workload may include multiple simultaneous emergencies and women and their babies with complex needs. To prioritise safely, an obstetrician needs to act as a leader, communicate and delegate appropriately, work within the multi-disciplinary team, and all whilst maintaining situational awareness.